Volcanic Emissions, Plume Dispersion, and Downwind Radiative Impacts Following Mount Etna Series of Eruptions of February 21–26, 2021. Issue 6 (17th March 2023) - Sellitto, P.; Salerno, G.; Corradini, S.; Xueref‐Remy, I.; Riandet, A.; Bellon, C.; Khaykin, S.; Ancellet, G.; Lolli, S.; Welton, E. J.; Boselli, A.; Sannino, A.; et al.
Abstract: During the extended activity of Mount Etna volcano in February–April 2021, three distinct paroxysmal events took place from February 21 to 26, which were associated with a very uncommon transport of the injected upper‐tropospheric plumes toward the north. Using a synergy of observations and modeling, we characterized the emissions and three‐dimensional dispersion for these three plumes, monitored their downwind distribution and optical properties, and estimated their radiative impacts at selected locations. With a satellite‐based source inversion, we estimate the emitted sulfur dioxide (SO2 ) mass at an integrated value of 55 kt and plumes injections at up to 12 km altitudes, which qualifies this series as an extreme event for Mount Etna. Then, we combine Lagrangian dispersion modeling, initialized with measured temporally resolved SO2 emission fluxes and altitudes, with satellite observations to track the dispersion of the three individual plumes. The transport toward the north allowed the height‐resolved downwind monitoring of the plumes at selected observatories in France, Italy, and Israel, using LiDARs and photometric aerosol observations. Volcanic‐specific aerosol optical depths (AODs) in the visible spectral range ranging from about 0.004 to 0.03 and local daily average shortwave radiative forcing (RF) ranging from about −0.2 to −1.2 W m −2 (at the top of atmosphere) and from about −0.2 to −3.0 W m −2 (at the surface) are found. The composition (possible presence of ash), AOD, and RF of the plume have a large inter‐plume and intra‐plume variability and thus depend strongly on the position of the sampled section of the plumes. Plain Language Summary: The volcanic plumes from Mount Etna's eruptions disperse usually toward the east, to the Central‐Eastern Mediterranean, where ground stations are not available to monitor and characterize them. During the extended intense volcanic activity of Mount Etna in February–April 2021, some of the plumes dispersed toward the north, in an area where many and well‐equipped ground observatories are available. This was a unique opportunity to study the emissions, dispersion dynamics, shape/composition, and impacts of Mount Etna's aerosol plumes. We analyzed these rare events using many information layers: satellite observations, numerical simulation of the plume's dispersion, and downwind ground‐based observatories. By coupling these information pieces, we could reconstruct these events and untangle their impacts from those of a major Saharan dust outbreak that occurred simultaneously. These events were found quite extreme for Mount Etna (extreme emissions and high altitude—around 12 km). We found that this type of extreme Etna's eruptions has a relevant (and not yet studied) impact on the atmospheric composition and regional climate in the Mediterranean area. The plumes, after continental dispersion, exhibit a complex filamentary shape and a complex aerosol composition and properties, due to the presence of both sulfur‐containing particles and ash. Key Points: Three distinct paroxysmal events took place at Mount Etna from February 21 to 26, 2021 and the plumes were transported toward the north Plumes dispersion is characterized with Lagrangian modeling initialized with measured SO2 emissions and with satellite observations A series of LiDARs detected and characterized the plumes downwind and their observations are used to estimate the plumes radiative forcing